Healthcare and environmental issues in the Arab states: crafting policy tracks. (2012) - Anwar, Syed Aziz
The issues of environment, healthcare and development are important to academics, citizens, firms and of course policy-makers. In recent years, some studies done particularly by The World Health Organization (WHO) and World Bank have sought to enhance our understanding of the causes of deteriorating environmental conditions and their potential consequences for healthcare and economic development at large. While insightful, these studies have largely ignored the multiple policy tracks that need to be designed by the Arab states to address pressing issues relating to environment, healthcare and economic development. We argue in this paper that the Arab states do not necessarily face similar issues and hence multiple policy tracks need to be considered for addressing those issues. Our empirical investigation revealed differences in perception about the issues addressed in this study.